Analisi Pengaruh Kualitas Produk dan Daya Saing Produk Dalam Meningkatkan Nilai Penjualan Pada Industri Anyaman Ketak (Studi Kasus di Dusun Nyiurbaya Gawah Kec. Lingsar) - Masruron, Muhammad; Vinuzia, Mala; Ilyana, Patisa (Fakultas Syariah IAI Hamzanwadi Pancor, Lombok Timur, Indonesia, 2025)
This study aims to analyze the effect of product quality and product competitiveness on sales value in the ketak woven industry in Nyiurbaya Village, Lingsar District. There are three formulations of the problem studied: (1) the effect of product quality significantly on sales value, (2) the effect of product competitiveness significantly on sales value, and (3) the effect of product quality and product competitiveness significantly on sales value. The method used in this study is multiple linear regression analysis. The results of the partial test (T test) show that the product quality variable (X1) has a significant value of 0.00, <0.05, with a t-count of 7.040> t-table 1.991, so that product quality has a significant effect on sales value. The product competitiveness variable (X2) also shows a significant value of 0.00, <0.05, with a t-count of 6.169> t-table 1.991, so that product competitiveness also has a significant effect on sales value. The results of the simultaneous test (F test) show that the significant value is 0.00 <0.05 with an F-count of 40.489> F-table 3.12, which means that product quality and product competitiveness together have a significant effect on sales value. The coefficient of determination (R²) value of 0.513 indicates that 51.3% of the variation in sales value can be explained by product quality and competitiveness, while the rest is influenced by other factors not included in this study.